2016
DOI: 10.3892/ijo.2016.3586
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of the anti-programmed death-1 antibody on human peripheral blood mononuclear cells

Abstract: Immune checkpoint antibody-mediated blockade has gained attention as a new cancer immunotherapy strategy. Accumulating evidence suggests that this therapy imparts a survival benefit to metastatic melanoma and non-small cell lung cancer patients. A substantial amount of data on immune checkpoint antibodies has been collected from clinical trials; however, the direct effect of the antibodies on human peripheral blood mononuclear cells (PBMCs) has not been exclusively investigated. In this study, we developed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Interestingly, it was shown that anti-PD-1 antibodies themselves seem to have a direct effect on peripheral blood mononuclear cells (PBMC) from cancer patients. It was reported that anti-PD-1 antibodies stimulated in vitro PBMC proliferation induced by anti-CD3 antibodies and inhibited the induction of MDSC in the same experimental settings ( 87 ).…”
Section: Combination Of Ici and Mdsc Neutralizationmentioning
confidence: 94%
“…Interestingly, it was shown that anti-PD-1 antibodies themselves seem to have a direct effect on peripheral blood mononuclear cells (PBMC) from cancer patients. It was reported that anti-PD-1 antibodies stimulated in vitro PBMC proliferation induced by anti-CD3 antibodies and inhibited the induction of MDSC in the same experimental settings ( 87 ).…”
Section: Combination Of Ici and Mdsc Neutralizationmentioning
confidence: 94%
“…Immunotherapy and kinase inhibitors are nowadays the backbone of systemic therapy, while chemotherapy is considered a second-line, or even further, treatment option ( 94 96 ) ( Fig. 2 ).…”
Section: Principles Of Medical Treatmentmentioning
confidence: 99%
“…Cell proliferation assay. Cell proliferation was examined using the WST-1 assay (Dojin Kagaku Corp., Kumamoto, Japan) as described previously (2). Briefly, 1 × 10 4 SCC-3 cells were seeded in a 96well microculture plate (Corning Inc., Corning, NY), and compounds at concentrations ranging from 0.25 to 100 μM were added.…”
mentioning
confidence: 99%